Anthrax: Epidemiological and Epizootiological Situation in 2015, Prognosis for 2016 - A. G. Ryazanova; L. Yu. Aksenova; N. P. Buravtseva; T. M. Golovinskaya; E. I. Eremenko; O. I. Tsygankova; N. G. Varfolomeeva; A. N. Kulichenko (Проблемы особо опасных инфекций, 2016)
Outlined are the results of assessment of epidemiological and epizootiological situation on anthrax across the globe in 2015. Three human cases of cutaneous anthrax were registered in the Russian Federation. Detected were two epizootic foci with three cases of live-stock animal disease. 1-20 cases of anthrax in humans are forecasted in the Russian Federation in 2016. Adverse as regards anthrax situation is created in a number of near and far abroad counties. The highest morbidity rates among animals and humans are reported from Asian and African countries. Discussed are the results of investigation into the blunder of the US Department of Defense laboratory system, resulted in distribution of ineffectively decontaminated samples of anthrax agent to the US laboratories, as well as of other states within the past twenty years.